2018
DOI: 10.3906/bot-1712-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of photosynthetic parameters on species acclimation in an arid mountainous region of China

Abstract: Understanding the mechanisms of how environmental factors limit species distribution along environmental gradients is a central question in ecology. This study aimed to understand species acclimation in view of photosynthetic parameters in an arid mountainous region. We measured some photosynthetic parameters and light and CO 2 photosynthesis response curves for all plant communities with seven dominant species in 13 sites along an elevation gradient in the Qilian Mountains in arid northwestern China. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…So, our results suggested that F1 hybrids may keep high growth rate and great biomass production through extend leaf life spans. In addition, the results of membership function comprehensive assessment also supported that F1 hybrids performed well as their parents ( [37,38]. In the present work, F1 hybrids showed the parallel LCP and LSP levels compared to their parents with no significant differences (P 0.05; Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…So, our results suggested that F1 hybrids may keep high growth rate and great biomass production through extend leaf life spans. In addition, the results of membership function comprehensive assessment also supported that F1 hybrids performed well as their parents ( [37,38]. In the present work, F1 hybrids showed the parallel LCP and LSP levels compared to their parents with no significant differences (P 0.05; Table 2).…”
Section: Discussionsupporting
confidence: 81%